Morphological and molecular description of Sarcocystis ratti n. sp. from the black rat (Rattus rattus) in Latvia - Prakas, Petras; Kirillova, Viktorija; Gavarāne, Inese; Grāvele, Evita; Butkauskas, Dalius; Rudaitytė-Lukošienė, Eglė; Kirjušina, Muza (Parasitology Research, 2019)
Rodents have been widely studied as intermediate hosts of Sarcocystis; however, only a few reports on these parasites in the black rat (Rattus rattus) are known. Having examined 13 black rats captured in Latvia, sarcocysts were found in skeletal muscles of two mammals and were described as Sarcocystis ratti n. sp. Under a light microscope, sarcocysts were ribbon-shaped, 0.9-1.3 x 0.09-0.14 mm in size and had a thin (0.8-1.3 mu m) and smooth cyst wall. The lancet-shaped bradyzoites were 8.3 x 4.3 (7.5-9.3 x 3.9-4.8) mu m. Under a transmission electron microscope, the cyst wall was up to 1.3 mu m thick, wavy, the ground substance appeared smooth, type 1a-like. Morphologically, sarcocysts of S. ratti were somewhat similar to those of S. cymruensis, S. rodentifelis, and S. dispersa-like previously identified in the brown rat (Rattus norvegicus). On the basis of 18S rDNA, 28S rDNA, and cox1, significant genetic differences (at least 2.3, 4.5, and 5.8%, respectively) were observed when comparing S. ratti with other Sarcocystis species using rodents as intermediate hosts. While ITS1 sequences of S. ratti were highly distinct from other Sarcocystis species available in GenBank. Phylogenetic and ecological data suggest that predatory mammals living near households are definitive hosts of S. ratti.